PSEUDOMONAS AERUGINOSA-INDUCED ACUTE EXOGENOUS ENDOPHTHALMITIS POST-CATARACT SURGERY - Akbar, Muhammad Khalil; Nilawati, Enny (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2023)
Introduction: The Endophthalmitis Vitrectomy Study revealed that only a small percentage of endophthalmitis cases, specifically 4.1%, were caused by Gram-negative organisms, and the most frequent of these was Pseudomonas aeruginosa. Moreover, poor visual outcomes were consistently linked to this bacterium. Objective: To provide knowledge regarding Pseudomonas aeruginosa as a cause of exogenous endophthalmitis and its management. Case Illustration: A 65-year-old male was admitted to the Emergency Department due to pain and blurred vision in his left eye. After cataract surgery, three days prior, these symptoms had been present for four days. The patient had conjunctival redness, corneal edema, posterior synechia of the iris, and very low visual acuity in the affected eye. A B-mode ocular ultrasonography revealed a considerable vitreous opacity and an aberrant echo in the left eye, suggesting endophthalmitis in the patient. The patient underwent emergency surgery immediately, including Pars plana vitrectomy (PPV), Silicon oil, IOL extraction, and intravitreal antibiotics injection. Moreover, Pseudomonas aeruginosa was found in the vitreous by a smear test and culture process. On the first day after the surgery, the patient's vision improved to light perception but with incorrect projection. A Fundus exam showed an attached retina with silicon oil and no macular edema. After one month, the patient's visual acuity improved to 2/60. Conclusions: Identifying the causative organisms in infectious endophthalmitis is critical in determining treatment and visual results. Pars Plana Vitrectomy (PPV) followed by intravitreal injection of antibiotics as the